2018
DOI: 10.1128/iai.00041-18
|View full text |Cite
|
Sign up to set email alerts
|

Adipocyte Model of Mycobacterium tuberculosis Infection Reveals Differential Availability of Iron to Bacilli in the Lipid-Rich Caseous Environment

Abstract: Mycobacterium tuberculosis, a successful human pathogen, utilizes multiple carbon sources from the host but adapts to a fatty-acid-rich environment in vivo. We sought to delineate the physiologic response of M. tuberculosis to a lipid-rich environment by using differentiated adipocytes as a model system. Global transcriptome profiling based on RNA sequencing was performed for bacilli from infected adipocytes and preadipocytes. Genes involved in de novo fatty acid synthesis were downregulated, while those predi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 57 publications
1
11
0
Order By: Relevance
“…In addition, we have shown that besides sterols, long-chain fatty acids (LC-FA) are also key participants as components of the Mtb metabolism inside the host since Mtb cultured at stationary phase in the presence of LC-FA induced a dormant phenotype (i.e., accumulation of lipid droplets, increase of drug tolerance and low metabolic activity) (Rodríguez et al, 2014). In agreement with our previous results, Nandy and co-workers showed that the metabolism of oleic acid leads to a reductive cytosol in Mtb , which counteracts oxidative stress in a caseous-necrotic environment displayed by adipocytes (Nandy et al, 2018). These results strongly suggest that Mtb is adapted to a lipid environment in vivo .…”
Section: Introductionsupporting
confidence: 93%
“…In addition, we have shown that besides sterols, long-chain fatty acids (LC-FA) are also key participants as components of the Mtb metabolism inside the host since Mtb cultured at stationary phase in the presence of LC-FA induced a dormant phenotype (i.e., accumulation of lipid droplets, increase of drug tolerance and low metabolic activity) (Rodríguez et al, 2014). In agreement with our previous results, Nandy and co-workers showed that the metabolism of oleic acid leads to a reductive cytosol in Mtb , which counteracts oxidative stress in a caseous-necrotic environment displayed by adipocytes (Nandy et al, 2018). These results strongly suggest that Mtb is adapted to a lipid environment in vivo .…”
Section: Introductionsupporting
confidence: 93%
“…Interestingly, the fadE5 gene (rv0244c) in addition to pks5, papA3, pE, and fadD23 genes have been recently involved in the synthesis of the complex lipid trehalose polyphleate (TPP) closely related in structure to SL-1 and PAT may be involved in membrane fluidity [38]. The fadE5 and pks2 genes were reported to be differentially expressed in the differentiated triglyceride-rich 3T3L1 human adipocyte cell line infected with Mtb H37Rv compared to the nondifferentiated cells [39]. Since the fadE5 gene has been previously found to be essential for in vitro growth in cholesterol [40], it has been proposed that upregulation of fadE5 and pks2 may be related to the cholesterol-rich environment found in necrotic adipocytes [39].…”
Section: Main Transcriptomic Changes Between Ut127 and Ut205mentioning
confidence: 99%
“…The fadE5 and pks2 genes were reported to be differentially expressed in the differentiated triglyceride-rich 3T3L1 human adipocyte cell line infected with Mtb H37Rv compared to the nondifferentiated cells [39]. Since the fadE5 gene has been previously found to be essential for in vitro growth in cholesterol [40], it has been proposed that upregulation of fadE5 and pks2 may be related to the cholesterol-rich environment found in necrotic adipocytes [39]. We also found upregulation of the fadD6/FACL6 (rv1206) and echA2 (rv0456c) genes in the UT205 strain compared to Mtb H37Rv.…”
Section: Main Transcriptomic Changes Between Ut127 and Ut205mentioning
confidence: 99%
“…Mtb has been known to adapt to a fatty-acid-rich environment of the cell [41]. It has also been experimentally proved that cellular organelles which store host lipids, are actively manipulated by Mtb during active TB [42]. This change is reflected in mitochondrial pathways as cells change their metabolism towards fatty acids, which are actively enriched in our data set of DE protein-coding mRNAs.…”
Section: Discussionmentioning
confidence: 81%